Capillary microscopy in Europeans with idiopathic Moyamoya angiopathy. (16th March 2020) - Sander, Oliver; Schwitalla, Jan Claudius; Ringelstein, Marius; Aktas, Orhan; Schneider, Matthias; Berlit, Peter; Hartung, Hans‐Peter; Albrecht, Philipp; Kraemer, Markus
Abstract: Objective: In Europe, MMA is a very rare non‐inflammatory vasculopathy. MMA is an important differential diagnosis of cerebral vasculitis. Systemic manifestations, such as livedo racemosa or renal artery stenosis, associated with Moyamoya variants suggest the involvement also of non‐cerebral vessels. Hypothetically, capillary microscopy could be a promising non‐invasive screening method to visualize microcirculation, for example prior to cerebral angiography. Methods: Standardized capillary microscopic images were taken in European patients with MMA and subsequently evaluated in a blinded analysis, using data obtained from a large NP cohort and a large SLE cohort by the same blinded Investigator as controls. Results: Twenty‐four European MMD patients and 14 healthy accompanying controls were included in this study. The results were compared to 116 SLE patients and 754 NP subjects. In MMD patients, no capillary morphological differences were found in comparison with NP, in particular no density reduction or increased neoangiogenesis. The pattern observed in the SLE cohort was clearly distinct from NP and MMD with regard to vascular density, vascular damage, and neoangiogenesis. Conclusions: MMD is not associated with microvascular changes of the nailfold capillaries. In this respect, it is clearly distinct from SLE.